If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.2-3b/2+b/5=0.6-2b/5
We move all terms to the left:
0.2-3b/2+b/5-(0.6-2b/5)=0
We add all the numbers together, and all the variables
-3b/2+b/5-(-2b/5+0.6)+0.2=0
We get rid of parentheses
-3b/2+b/5+2b/5-0.6+0.2=0
We calculate fractions
There is no solution for this equation
| 6c=18c= | | 8y-3=5(y-1)/3y | | -4(x-2)=2-x | | X=10+5x4 | | z=z–3+5 | | 4x+4=-1+5x | | 3(p+4)=(2p+5) | | 40=-14x+4x | | X=10+5x3 | | 24-4x=7+4x | | 3÷5x+2=11 | | 4/x+2x=6 | | 4/x+2x=4 | | 0=x*2+8x-484 | | 3-4x-5=10 | | 75n=115n | | y=180-5y-18 | | 0.6x+2=11 | | y=180-(5y-18) | | 3y^2=17 | | 4.5+2y=6.1 | | 14+24n=35+17n | | 4+5n=6+3n | | 7m+3-4m=- | | 8y=-20 | | 8y=-20y | | F=n/1524,990 | | 2+5n=6+2n | | 67=13^x | | 60n=36 | | -13=7+7x | | x+x-1+x-2=x-2 |